Implementation of Money Waqf as a Contemporary Phenomenon In Indonesia - Ajeung Syilva Syara (STAI AL-FALAH CICALENGKA, 2021)
Waqf in Indonesia is generally in the form of land or buildings because the understanding of Muslims is limited to waqf of immovable objects even though in the Indonesian context, the Indonesian Ulema Council has issued a fatwa that allows the implementation of cash waqf. The benefits derived from conducting cash waqf are strengthening sharia banking, increasing sharia capital, driving the sharia economy, financing productive waqf assets, and supporting the implementation of social programs. This discussion will discuss the implementation of cash waqf in Indonesia. The results show that cash waqf in Indonesia has been recognized since the issuance of the fatwa on cash waqf by the DSN MUI in 2002. The fatwa contains five important points. First, cash waqf is waqf carried out by a person, group of people, institutions or legal entities in the form of cash. Second, including the notion of money is securities. Third, cash waqf is legal, while fourth, cash waqf can only be channeled and used for things that are permitted by syar'i and fifth, the principal value of cash waqf must be guaranteed for its sustainability, it may not be sold, donated, and or inherited. Keywords: Cash Waqf, Law, Islam Abstrak Wakaf di Indonesia pada umumnya berupa tanah atau bangunan karena pemahaman umat Islam terbatas pada wakaf benda tak bergerak padahal dalam konteks Indonesia, Majelis Ulama Indonesia telah mengeluarkan fatwa yang memperbolehkan dilaksanakannya wakaf uang. Manfaat yang diperoleh dari melakukan wakaf uang adalah memperkuat perbankan syariah, memperbesar permodalan syariah, menggerakkan ekonomi syariah, membiayai aset wakaf produktif, dan mendukung pelaksanaan program sosial. Pada pembahasan ini akan dibahas implementasi wakaf uang di Indonesia. Hasil Penelitian menunjukkan bahwa wakaf uang di Indonesia mulai dikenal sejak dikeluarkannya fatwa wakaf uang oleh DSN MUI pada 2002. Fatwa itu berisi lima point penting. Pertama, Wakaf uang adalah wakaf yang dilakukan seseorang, kelompok orang, lembaga atau badan hukum dalam bentuk uang tunai. Kedua, termasuk ke pengertian uang adalah surat-surat berharga. Ketiga, wakaf uang hukumnya boleh, sedangkan keempat, wakaf uang hanya boleh disalurkan dan digunakan untuk hal-hal yang dibolehkan secara syar’i dan kelima, nilai pokok Wakaf Uang harus dijamin kelestariannya, tidak boleh dijual, dihibahkan, dan atau diwariskan. Kata Kunci: Wakaf Uang, Hukum, Islam